Empowering Financial Decision-Making for Indonesian Migrant Workers in Hong Kong - Randi Bayu Prathama; Liza Handoko; Stevanny (Universitas Pelita Harapan, 2024)
This community service activity initiated by Faculty of Economics and Business Universitas Pelita Harapan (UPH), in partnership with Enrich Hong Kong has successfully conducted webinar for Indonesian Migrant Workers in Hong Kong. This webinar tried to enhance financial literacy and deepen understanding of savings as part of their financial planning for long-term goal. This initiative provides insight and practical guidance for managing personal financial management, to set financial goals. The webinar tries to bring the concept to practice by giving some scenarios that match the profile of the participants that were captured through a survey prior to the event. This webinar brought interactive discussion to better connect with the participants. This is a continuous activity to ensure that there’s impact toward the participants.